Analisis faktor-faktor yang mempengaruhi Kinerja pegawai pada dinas kesehatan Kabupaten kutai timur - Meita Sondang Rizki (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2016)
The study tries to identify to what extent incentive, competence, motivation, discipline, work environment, social security, nutrition and health of staff Health Department, it will also identify which factors give the most impact toward staff performance. This research excepted to benefit to all side, especially for institution head to dig elements that increasing performance of staff Health Department in Sangatta. Analysis model used to prove hypothesis is model analysis multiple linier regression that be analysed with using statistics computer program package, that is SPSS v. 14.0 for Windows. Responden that becoming objective this research are counted 75 of staff Health Department. Result of statistics analysis show that coefficient of the free variables regression, that is involvement factor in incentive (X1) = 0,164, competence (X2) = 0,178, motivation (X3) = 0,148, discipline (X4) = 0,048, work environment (X5) = 0,287, social security (X6) = 0,176, nutrition and health (X7) = 0,130, and constanta equal to 0,366. Equation of multiple linier regression is : Y = 0,366 + 0,164 X1 + 0,178 X2 + 0,148 X3 + 0,048 X4 + 0,287 X5 + 0,176 X6 + 0,130 X7 Conclusion that receive that level of influence explained by incentive, competence, motivation, discipline, work environment, social security, nutrition and health as independent variable impact toward performance of staff Health Department equal to correlation coefficient (R), that is 0,869 and level of depended performance to seventh of free variables above is equal to determination coefficient value (R2) that is 0,755 or 75,5 %. Result of analysis F – test indicate that all free variables by together have significant influence toward performance of staff Health Department. By parsial, variable incentive, competence, motivation, work environment, social security, nutrition and health have significant influence to performance of staff Health Department. Only one variable is discipline have no significant. Variabel independent have dominant influence to performance of staff Health Department is work environment (X5).